2009
DOI: 10.1103/physrevlett.102.162503
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New Broad Resonance inNe19: Implications for the Destruction of the Cosmicγ-Ray Emitteret al.

Abstract: Six proton-emitting states in 19Ne were studied through the inelastic scattering reaction H(19Ne,p);{19}Ne; (p)18F. Their energies and widths were derived from the protons detected at zero degree, while proton-proton angular correlations between the detector at zero degree and a segmented annular detector were used to determine their spin value. In addition to the known states, a new broad J=1/2 resonance has been evidenced at E_{x} approximately 7.9 MeV, approximately 1.45 MeV above the proton emission thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 21 publications
5
23
1
Order By: Relevance
“…Feature C has previously been observed several times [6,7,18,19], but while there is reasonable agreement in energy and proton width, the present fit suggests a significantly broader alpha width than the earlier works, even given their disagreement. Re-analysis of the data in Murphy et al [7] has revealed an ambiguity such that a significantly broader alpha partial width than reported would also adequately describe the structure.…”
Section: Resultscontrasting
confidence: 46%
See 4 more Smart Citations
“…Feature C has previously been observed several times [6,7,18,19], but while there is reasonable agreement in energy and proton width, the present fit suggests a significantly broader alpha width than the earlier works, even given their disagreement. Re-analysis of the data in Murphy et al [7] has revealed an ambiguity such that a significantly broader alpha partial width than reported would also adequately describe the structure.…”
Section: Resultscontrasting
confidence: 46%
“…The feature labelled B is likely to be the resonance previously observed by Bardayan et al [14], and by Dalouzy et al [6] (see Table I for observed energies and widths). The energy reported here is somewhat lower than previously observed, though it is poorly constrained as is illustrated by the large covariance between the energy and relative widths of this state.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations